Sphingolipids in parasitic protozoa - Zhang, Kai (2010)
The surface of most protozoan parasites relies heavily upon lipid-anchored molecules, to form protective barriers and play critical functions required for infectivity. Sphingolipids (SLs) play important roles through their abundance and involvement in membrane microdomain formation, as well as serving as the lipid anchor for many of these molecules, and in some but possibly not all species, as important signaling molecules. Interactions of parasite sphingolipid metabolism with that of the host may potentially contribute to parasite survival and/or host defense. In this chapter we summarize current knowledge of SL structure, synthesis and function in several of the major parasitic protozoan groups.